Computer Modelling of the Starting Processes of Induction Motor - Karaliūnienė, J.; Krikštaponis, L.; Lukošienė, D. (Elektronika ir Elektrotechnika, 2007)
The computer simulation of the starting processes of an induction motor is discussed. Differential equations of motor are presented. They are written on an axis α , β , o of coordinate system, connected with the fixed stator. The computer model of starting procedures is constructed in the environment of Matlab/Simulink, which is widely used in scientific and engineering practice. In order to create a model, the principle of objective programming is used. With created model it is possible to simulate direct starting processes of induction motor and the transient processes of rheostat start up. The model and processes of resistance starting are presented. The results of simulation shows that in the beginning of transient process appear the shock of starting currents and because of interaction of shock currents shock components of electromagnetic torque are created. Ill. 5, bibl.6 (in English; summaries in English, Russian and Lithuanian).